The Impact of Micro Influencers on Millennial Generation in the Consumption of Sustainable Products - Duarte, Alexandre (2022)
Vast literature has been demonstrating the importance that digital micro influencers have on the choices and purchase intentions of Millennial consumers, as well as, on the other hand, the growing concern about sustainability and the consumption of sustainable brands. This article analyzes this phenomenon, through a case study, seeking to understand the connection between the Millennial generation, micro influencers, and sustainable brands. A mixed methodology was chosen, with interviews with consumers and influencers, as well as a questionnaire survey, where the Mustique brand was analyzed, whose target is precisely this generation and which, in addition to the concern with sustainability, uses micro influencers in its communication. The results showed the positive impact of micro influencers on greater knowledge and consumption of sustainable products by Millennial consumers but pointed out the existence of other factors that end up impacting consumer decisions in their purchase decision process.